How to Address Politics of the Body in Participatory Performance? On the Possibilities of Sensory Fields and Collective Body Techniques as Analytical Tools - Lahtinen, Joonas (Nordic Theatre Studies, 2015)
This article discusses the importance of and challenges in analyzing and contex- tualizing the ways of bodily participation in participatory performance practices. The writer suggests that the crucial ideological assumptions, as well as the processes of exclusion and inclusion of any participatory project, are not to be seen solely in their “goals” or “themes”, but, even more distinctly, in the modes of bodily participation that they employ. The writer presents a novel performance analytical framework that takes the bodily dimension – what is actually done to and expected from the bodies of the participants during the performance event – as the starting point for critical analysis. Drawing especially from Jacques Rancière’s and Marcel Mauss’s views of human perception and experience, the main concepts of this framework are ‘sensory fields’ and ‘collective body tech- niques’. The writer also shows how these concepts have informed his research on Lois Weaver’s performance What Tammy Needs to Know About Getting Old and Having Sex (2008).